Modification Structure of Cinnamaldehyde with Primary Amines by Reflux and Sonication Methods in the Presence of Sulfuric Acid as a Catalyst - Setyono, Hilda Alfiyani; Suryanti, Venty; Putri, Alfianita Utama; Koketsu, Mamoru (Science and Technology Indonesia, 2024)
Cinnamon is one of the most valuable natural resources that sustains life and exists freely in nature. Cinnamaldehyde is the primary compound in cinnamon oil. It has a unique structure that contains a benzene ring, an aldehyde group, and an unsaturated double bond. Cinnamaldehyde has been structurally modified to improve biological activity. In this research, cinnamaldehyde and nitrophenyl amines were reacted with sulfuric acid as a catalyst by refluxing and sonication. UV-Vis Spectroscopy, FT-IR, 1H-NMR, and 13C-NMR were used to validate the chemical structures. Thin-layer chromatography (TLC) revealed a new single spot formed by the reaction of cinnamaldehyde and 4-amino-2-nitrophenol. By refluxing for 2 hours or sonicating for 30 minutes, a novel imine chemical, 4-nitro-2-((3-phenylallylidene)amino)phenol, was effectively synthesized with a yield of 75.21% or 83.71%, respectively. This imine was obtained as a dark red powder with a melting point of 237 °C. Meanwhile, only sonication produced a novel product from the reaction of cinnamaldehyde and 4-nitroaniline. However, the structural elucidation has not yet been performed because the yield was so low. Surprisingly, there was no reaction between cinnamaldehyde and 2,4-dinitroaniline. It was most likely owing to the amine’s bulky structure and the presence of two nitro groups in the amine as electron-withdrawing groups that reduced the nucleophilicity of the amine. We demonstrated that sonication is a suitable approach for imine synthesis, as it is commonly utilized in organic compound synthesis protocols.